Activity of Lithuanian St. Casimir society in the districts of Vilniaus region - Ereminas, Gintautas (Genocidas ir rezistencija, 2023)
This publication present effort of Lithuanian St. Casimir society to organize education of Lithuanians in territory controlled by Poland. Activity of divisions of Lithuanian St. Casimir society in Grybiškis, Stalgonys in Dieveniškis district is reconstructed.